Antibiotic Exposure during the Preceding Six Months Is Related to Intestinal ESBL-Producing Enterobacteriaceae Carriage in the Elderly - Man Zhang; Xiaohua Qin; Baixing Ding; Zhen Shen; Zike Sheng; Shi Wu; Yang Yang; Xiaogang Xu; Fupin Hu; Xiaoqin Wang; Yu Zhang; Minggui Wang (MDPI AG, 2022)
Intestinal carriage of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE carriage) poses a health risk to the elderly. It was aimed to study the prevalence and the risk factors of intestinal ESBL-PE carriage in the elderly. An observational study of a 921-elderly cohort was examined at health checkup for intestinal ESBL-PE carriage at a tertiary medical center in Shanghai. The prevalence and risk factors of intestinal ESBL-PE carriage, especially antimicrobial use in the preceding 9 months, were studied. The prevalence of intestinal ESBL-PE carriage was 53.3% (491/921) in community-dwelling elderly people. A total of 542 ESBL-producing isolates, including E. coli (n = 484) and K. pneumoniae (n = 58), were obtained. On genotyping, the CTX-M-9 ESBL was the most prevalent for 66.0% (358/542) of all isolates. Multivariate analysis showed that antibiotic exposure, age (61-70 years), and nursing home residence were independent risk factors of the ESBL-PE carriage. The analysis on the monthly use of antimicrobials showed that antibiotic exposure during the 6 months prior to sample collection contributed to the high prevalence of ESBL-PE carriage. A single exposure to an antimicrobial increased the risk of the carriage significantly, and the risk increased with the frequency of antimicrobial exposure (RR, 1.825 to 5.255). Prior use of second or third generation cephalosporins, fluoroquinolones, and macrolides increased the risk of the carriage. The results of this study indicate the importance of using antimicrobials judiciously in clinical settings to reduce antimicrobial resistance. Further studies with multiple center surveillance and with comparison of ESBL-PE carriage in the elderly and in the general population simultaneously are needed.